Extended soil surface drying triggered by subsurface drip irrigation decouples carbon and nitrogen cycles and alters microbiome composition - Griffin-LaHue, Deirdre; Wang, Daoyuan; Gaudin, Amélie C. M.; Durbin-Johnson, Blythe; Settles, Matthew L.; Scow, Kate M. (Frontiers in Soil Science, 2023)
Introduction: Irrigation management dramatically alters soil water availability and distribution and could impact soil microbial communities and carbon (C) and nitrogen (N) cycling to an even greater degree than observed in rainfed systems. Adoption of subsurface drip irrigation (SDI) in California's Mediterranean agroecosystems provides agronomic benefits but wets only a portion of the soil volume near the root zone, leaving the rest dry throughout the growing season. In contrast, traditional furrow irrigation (FI) has periodic wetting events with more homogenous moisture distribution. With conversion to precision irrigation methods, how will the microbiome respond to changes moisture availability, and how is their response influenced by soil C and N resource levels? Methods: In a field experiment in California, we compared SDI and FI's effects on microbial communities and evaluated how long-term organic and conventional management systems impact outcomes. Throughout the growing season, soil samples were collected at two depths (0-15, 15-30 cm) and three distances from bed center (10, 25, 45 cm) where the drip tape is located.Results: At harvest, soils irrigated using SDI had lower microbial biomass C (MBC) than under FI at the surface and showed a build-up of soluble C and N relative to MBC at the bed edge, indicating reduced microbial uptake. Community composition at the bed edge also diverged between SDI and FI, favoring Actinobacteria in the former and Acidobacteria and Gemmatimonadetes in the latter. Regardless of irrigation type, dry areas of the bed had the highest alpha diversity indices. Response to SDI was similar in organic and conventional systems, though organic had higher MBC, DOC, and relative abundance of Proteobacteria and fungal lipids, regardless of irrigation.Discussion: Prolonged dry conditions in SDI appeared to limit microbial access to resources and changed community composition. As seen in non-agricultural systems, the severity and frequency of moisture changes, adaptation of the communities, and resource availability affect microbial response. Decoupling of C and N pools in dry surface soils under SDI may increase the potential for losses of DOC and nitrate with the first winter rains in this Mediterranean climate.